Levels and determinants of glycosylated hemoglobin (HbA1c) status among reproductive age women of Tripura, North East India - Subrata Baidya; Rituparna Das (Wolters Kluwer Medknow Publications, 2018)
Introduction: Glycosylated hemoglobin (HbA1c), a marker of chronic hyperglycemia, has been recommended for use, in the diagnosis of diabetes. Objective: To assess the mean HbA1c level among reproductive age women in Tripura and to study the factors associated with high HbA1c level (≥ 6.5 %). Material & Methods: This cross-sectional study was conducted in Tripura among 2000 reproductive age women selected by Cluster sampling using PPS technique. Results: The present study revealed that the mean HbA1c level was 5.29 + 0.83% among the reproductive age women with 3.95% participants having HbA1c level of ≥ 6.5%). Multiple logistic regression analysis revealed that the age group and income of the family had a significant effect on the HbA1c status. Scheduled tribe women had 0.43 odds (0.22-0.81) of having high HbA1cstatus compared to women from general caste. Conclusion: The present study provided the reference values for HbA1c distribution among reproductive age women in Tripura and may be useful in the early identification of at-risk individuals.